Optimizing extracellular matrix for endothelial differentiation using a design of experiments approach - Mikayla L. Hall; Wei-Han Lin; Brenda M. Ogle (Scientific Reports)
Abstract The extracellular matrix (ECM) plays a vital role in stem cell differentiation to endothelial cells in vivo and is also important for the specification of endothelial cells in vitro. Individual ECM components have previously been shown to support endothelial differentiation; here, we use a Design of Experiments approach to optimize ECM composition to more effectively drive endothelial differentiation. We found that a combination of Collagen I, Collagen IV, and Laminin 411 could induce endothelial differentiation well beyond that found with Matrigel, the most commonly used differentiation substrate for endothelial cells. We also show that the addition of vascular endothelial growth factor (VEGF) during differentiation improves outcomes and that transforming growth factor beta (TGFβ) inhibits specification. The optimized ECM formulation (EO) was subsequently used to create bioprinted constructs, demonstrating its ability to spatially define endothelial differentiation in 3D environments. Our results build our mechanistic knowledge of the signaling axes that regulate differentiation in response to ECM stimulation with practical implications for the vascularization of engineered tissues.